Semiconducting properties of nanofiber polyaniline organic semiconductor - Li, Yu; Al-Ghamdi, A. A.; Al-Hartomy, Omar A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Natl Inst Optoelectronics, 2012)
The electrical conductivity, optical and microstructure properties of the polyaniline nanofibers have been investigated. The SEM image of the polyaniline shows the formation of nanofibers with diameters of 30-50 nm and lengths, of 300-1000 nm. The electrical conductivity results indicate that the polyaniline is an organic semiconductor. The room temperature electrical conductivity of the polyaniline nanofibers was found to be 5.67x10(-4) S/cm. The electrical conductivity mechanism of the nanofibers polyaniline varies from the conduction by localized states to the conduction by extended states. In this nanofibers polymer, the current is carried by the movement of polarons partially delocalized on the polymeric structure. The optical band gap of the polymer was found to be 2.57eV of direct allowed transitions. The width of localized states for the polymer was found to be 0.30eV, which is from the conduction band edge to mobility edge.
Keywords: Organic semiconductor; polyaniline; nanofiber; electrical properties